Determination of Lichens’ Bioaccumulation Capacity for Radioactive Isotopes Under Laboratory Conditions as a Basis for Their Application as Biomonitors - Michał Saniewski; Michał Hubert Węgrzyn; Patrycja Fałowska; Patrycja Dziurowicz; Karolina Waszkiewicz; Tamara Zalewska (Applied Sciences)
This study investigates the bioaccumulation capacity of the lichen Cladonia uncialis for radioactive isotopes, aiming to establish its potential as a biomonitor. Conducted under controlled laboratory conditions, the experiment utilised gamma-emitting isotopes to simulate fallout. The lichens were exposed to varying concentrations of these isotopes in three aquariums. The results demonstrated that the bioaccumulation of 54Mn, 57Co, 60Co, 65Zn, 137Cs, and 241Am by C. uncialis was proportional to their initial deposition levels, and this occurred in the first days of the experiment. Analysis of isotope activity in washed and unwashed lichens showed that retention primarily occurred intracellularly, indicating effective bioaccumulation. The study derived the Aggregated Transfer Coefficient (Tag) for each isotope, which ranged from 0.34 to 0.64, and the absorption capacity of the elements increased in the following order: 54Mn < 57Co < 60Co ≤ 65Zn < 241Am < 137Cs. Absorption efficiency, amounting to approximately 50% for 137Cs and 241Am, highlights the potential for lichens to serve as reliable biomonitors for environmental monitoring and estimation of deposition when knowing only the activity of the isotopes in lichen.